The emergence and influence of group leaders in web-based collaborative writing: self-reported accounts of EFL learners. Issue 8 (23rd November 2021) - Selcuk, Hasan; Jones, Jane; Vonkova, Hana
Abstract: Web-based collaborative writing (CW) has been widely used in the field of English as a foreign language (EFL) during the last decade. Previous studies have mainly focused on how online platforms have facilitated the CW process for EFL learners, how web-based CW has shown progress in EFL learners' writing development, and how EFL learners in groups interact with one another during web-based CW. However, there are limited studies on web-based CW among Turkish EFL learners. The aim of this study was to analyse Turkish high school EFL learners' self-reported accounts of their writing process in English with the support of group leaders in a web-based CW activity. The key findings were that first, the groups found the need to elect a group leader to act as a facilitator for other group members, and that group members found their group leader's help in planning their writing tasks and corrective feedback useful for their learning; second, group leaders provided affective support during the writing activity, with group members reporting that praise and motivational phrases received from their group leaders increased their self-confidence and motivation towards writing in English. This study contributes to knowledge about improving high school EFL learners' writing through a web-based CW activity. The peer leadership approach is promising in supporting student's self-efficacy and self-regulation in learning and is easily applicable to teachers in other contexts who wish to promote writing activities outside of the classroom setting.